Health organizations' efficiency by data envelopment analysis. Health Direction IV, East Lima Micronets, 2003 - Ligarda, Juan (2006)
Objective: To evaluate health micronets (MN) in East Lima (Peru) using data envelopment analysis (DEA). Design: Descriptive, retrospective, transversal study. Setting: Lima Province, East Lima health establishments micronets. Interventions: Data on output included year 2003 promotional preventive activities (PPA) and number of attentions, and input included pharmaceutical expenses and personnel -doctor and other staff members. Materials: Data was obtained from East Lima Health Management IV. Main outcome measures: Inputs and outputs. Results: From the 17 MN only 9 obtained maximum global efficiency level 1 with range 0,87 to 1. For the pure technique efficiency, 11 MN obtained optimum efficiency, with range 0,91 to 1. With the same resources, MR1, MR8, MR9, and MR10 could increase the number of attentions in more than 10%, while PPA could increase in more than 14%. Conclusions: In the MN efficiency evaluation at least eight units showed some kind of inefficiency. DEA is a useful tool evaluation for both input and output and identifies units that are inefficient compared to others. Despite difficulties involved, the method appears to be beneficial for management. Future research should consider more accurate output and inputs measurements, appropriate available methods use and exploration on inefficiency causes.